Design, modeling, and performance comparison of feeding techniques for a microstrip patch antenna - Soh, P. J.; A. Rahim, Mohamad Kamal; Asrokin, A.; Abdul Aziz, M. Z. A. (Penerbit UTM Press, 2007)
Microstrip patch antennas has a variety of feeding technique applicable to them. It can be categorized in accordance to the main power transfer mechanism from the feed line to the patch. Contacting feeds investigated in this work are coaxial probe feed and transmission line feed; while noncontacting feeds which are proximity-coupled-fed and the aperture-coupled-fed. This work is an effort to design, model, simulate, fabricate and measure all four different types of microstrip antenna’s of noncontacting feed and contacting feed techniques on a similar sized, rectangular patch. Simulation is done using the circuit model (CM) derived from the Transmission Line Model (TLM), and is compared with another simulation set of feeding methods produced using the Method of Moments (MoM). Both methods are simulated on Microwave Office. This design intends to focus on studying the differences in measured and simulated parameters of the patch and its respective feeds, simulate it using MoM, and finally, the fabrication process. Radiation measurements are also presented. Designs for each feeding technique achieved the best return loss (RL) at the desired frequency range of 2.4 GHz. The fabricated hardware produced good RL, bandwidth (BW), and comparable radiation performance compared against simulation using MoM. All antennas produced maximum E-and H-plane co- and crosspolarization difference in the magnitude of -18 dB and half-power beam widths (HPBW) in the magnitude of 90o